La Scuola Se. Ovvero, la professione docente - Dozza, Liliana (Studi sulla Formazione/Open Journal of Education, 2011)
Another essay on Frabboni and its reflection on the question of education. An “open school inside-out open” is a definition that closely recalls the thought of the scholar of Bologna because it is an expression that tells how democracy is an open system that will require more education people who are intentionally involved the development of society and its education system. The school, of course, is made up of teachers and educators, professionals, competent, courageous innovators who undertake adifficult job The teacher is a builder and an architect, reaffirmsFrabboni, and pedagogical reflection can not forget to reflect on the historical and social transformation in recent years concerns the teaching profession.